Electronic dictionary entries with animated pictures: Lookup preferences and word retention - Lew, Robert; Doroszewska, Joanna (Oxford University Press, 2009)
In a well-known study, Laufer and Hill (2000) used an experimental electronic dictionary to investigate the lookup patterns and preferences of Israeli and Chinese learners of English and their effect on word retention. The present study attempts to replicate and extend Laufer and Hill's experiment with Polish learners of English. Animated images are introduced in an experimental online dictionary, and are tested on lexical items denoting facial expressions and body reflexes. Lookup patterns and lookup strategies are examined with regard to their impact on vocabulary retention. A strong negative effect of viewing animated images on vocabulary retention is found.
Keywords: vocabulary retention; dictionaries; animations; lexicographic data; definition; equivalent; examples